Assessing the concentration of heavy metals (lead, cadmium and nickel) in selected personal care products and urine among the targeted consumers - Masuri, Nurul Jasmine (Universiti Sains Malaysia, 2016)
Personal care products (PCP) are widely known and regularly used by people, often on a daily life, as well as in industry and commercial. In some countries, there are no strong regulations on safety of the ingredients. Some heavy metals are used in the personal care product as ingredients, even though most of them are contaminants. This study was conducted to assess the concentration of heavy metals in various types of PCP include deodorant, lipstick, shampoo, hand and body lotion and also in nineteen urine samples of the targeted consumer. Eight products of different brands which are locally and internationally available in the markets were analyzed. Determination of heavy metals was done by pre treatment of samples by acid digestion using concentrated Nitric Acid (HNO3) and Perchloric Acid (HCIO4), then the samples were analysed using Atomic Absorption Spectrophotometer (AAS), the statistical analysis were done by SPSS version 22. Results showed that, the highest mean concentration of metal lead, cadmium and nickel was in deodorant with 0.262 mg/L, lipstick with 0.005 mg/L and hand and body lotion with 0.048 mg/L respectively. There are no an association between the types and frequency of product use and the concentration of heavy metals Pb, Cd and Ni in urine on targeted consumer with (p > 0.05). Even though, the trace amount of heavy metal were under the permissible limit, it might have some contributing factors that related in concentration of heavy metal in urine such as smoking status, nutritional status, drinking water, exposed to smoke vehicle and etc. All the metals are present and under the safe limits after carried out in selected brands of PCP.